(3cJGH UhQ GdchGcHs - (3YHO GdQMef Hf YeQ Hf Sgd GdUhaj GdQGRqj, CHh GdMSjf,J (B376 (3g` s ((3hGKb Hf Ydi Hf YeQ Hf GdMSjfi GdeYQha HGHf GdThci s)
(3ChdgG (B:s
(3HYO GdOjHGLg (B: (3Efi QCjJ cKjQkG ef GdfGS jNhVhf ai WdH eYQag GdchGcH GdKGHJg s
(3BNQgG (B:s
(3bd GdMeO (B: (3JeJ GdUhQ GdLfhHjI hgj NeS YTQg UhQg aHJeGegG Je GdcJGH s
(3fSNgG GHf GdThci ef fSNI GdTjN CHj WGgQ YHO GdHGbi hdO GdTjN GdEeGe GdBhMO eDjO YUQg CHj HcQ eMeO Hf YHO GdHGbi Hf eMeO Hf YHO Gddgs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B319 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B162s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B72 s
Keywords: (3Gdadcs